The programmatic elite in German health policy: Collective action and sectoral history. (July 2020) - Hornung, Johanna; Bandelow, Nils C
Do biographies of policy elites make a difference for the policy process and output? Leading theories of the policy process focus on other explanations that mostly have been derived from peculiarities of American politics. This article transfers a French approach to the study of policy processes in German health policy. It emphasizes how this French perspective presents an added value in the form of the programmatic action framework. At its core, the programmatic action framework proposes that programmatic elites in policy sectors form on the basis of shared biographical intersections and connect to a joint program. Applying the programmatic action framework to the German case of a programmatic elite in health policy that dominated the last quarter-century of major reforms, the analysis reveals the explanatory power of the programmatic action framework in other political contexts. A transfer of the programmatic action framework to other countries and policy issues, however, must respect the specificities of the political system and policy subsystem. In Germany, the specific role of self-governance enhances the analytical categories of the programmatic action framework, moving beyond the traditional conflict between custodians and austerians of state.